Research of temperature distribution in rooms with radiant heating systems; MATEC Web of Conferences; Vol. 194 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2018) - Voloshko I. Ivan (Les Ulis, EDP Sciences, 2018)
Title screen